The EP Energy Function and Minimization Schemes - Minka, Tom (2007)
This note discusses the EP energy function in both its primal and dual forms and the connection to the Bethe free energy. It gives a theoretical justification of damping algorithms as well as a simple representation of Yuille's double-loop algorithm.